Vitamin B Complex and Homocysteine Levels - A Trend Study Among Asian Indians - Iyer, Sandhya; Sinkar, Prachi; Krishnakumar, K; K, Kallathikumar; Velumani, Amruta (Asian Journal of Medical Sciences, 2019)
Background: Vitamin B complex levels have been strongly correlated with homocysteine status and many studies suggest supplementation with vitamin B to lower cardiovascular risk among adults. However, this relationship does not show a direct trend with many studies concluding otherwise. Aims and Objective: Our report is an attempt to study association between levels of vitamin B6, folate and B12 in relation to homocysteine in a Pan-India cohort of over 5000 individuals. Materials & Methods: Data from a total of 5487 Asian Indians including 2942 males and 2545 females were considered for this study. Analysis for levels of vitamins B6 and folate was done using the technology of Liquid Chromatography - Mass Spectrometry (LC-MS), while that for Vitamin B12 and homocysteine was done using the Chemiluminescence Immunoassay (CLIA). Results: Our analysis identified a clear correlation between vitamin B12 status and levels of homocysteine, while no such trend was observed with vitamin B6 and folate. The total frequency of vitamin B12 deficiency was detected to be 25% of which 50% exhibited clinically high homocysteine levels. The frequency among males was found to be high at 61.6% in comparison to females at 32.3% with the difference being statistically significant at p<0.0001. Conclusion: Our report is one of the first few to document levels of vitamin B6, folate and B12 in relation to homocysteine in a large Asian Indian cohort. Low levels of vitamin B12 was found to have a greater impact on Hcy levels in comparison to other B-vitamins studied.